PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS ARTICULATE STORYLINE PADA PEMBELAJARAN TEMATIK KELAS IV SEKOLAH DASAR - Listiyawati, Listiyawati; Hendracipta, Nana; Nurhasanah, Ana (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2025)
This study aims to examine the development process, feasibility, and students’ responses to interactive media based on Articulate Storyline in thematic learning for fourth-grade elementary school students. The study employed the 4D development model, which consists of four stages: define, design, develop, and disseminate. The instruments used included interview sheets, observation sheets, validation questionnaires, and student response questionnaires. The results of this media development research showed an average percentage score of 89.5% from media experts, 92.85% from content experts, and 95% from language experts—all categorized as “highly feasible.” In addition, the student response questionnaire yielded a score of 95%, categorized as “very good.” Based on these results, it can be concluded that the interactive learning media based on Articulate Storyline for thematic learning in fourth-grade elementary school has been successfully developed, is feasible for use in the learning process, and received positive responses from students after being implemented in the classroom.